Reading: The students’ pleasure - Cardozo Rincón, Gerardo (Rastros Rostros, 2015)
Purpose: this article publishes the results of a piece of research that was conducted with high school students in a municipality of Boyacá, Colombia. This work’s main objective was to promote reading since it is considered essential in the comprehensive training of people. Description: some shared and repeated ideas about reading in academia have been critically considered. This led the theoretical foundation to give prominence to some approaches that revive the concept of reading as a fully pleasant exercise. Point of view: likewise, according to the results obtained, such generalized statements that obscure the artistic and enjoyable value of this activity have been discussed.Conclusions: finally, the results suggest that the strategies to strengthen reading are not unfamiliar or complex, but do require specific attitudes such as recognizing the student’s individual tastes and rethinking the undisputed reading of some books considered mandatory
Keywords: students; comprehensive education; reader; reading; pleasure